Piceatannol as a potential antiviral agent against vaccinia virus at multiple stages - Zhang, Liyuan; Liu, Yuwen; Li, Daoqun; Luan, Junwen; Zhang, Leiliang (Frontiers in Microbiology, 2026)
The resurgence of mpox, caused by the mpox virus (MPXV), has intensified the demand for effective antiviral agents. This study evaluates the antiviral activity of piceatannol, a natural polyphenol, utilizing vaccinia virus (VACV) as a model due to the genetic conservation between the two viruses. In vitro experiments demonstrated that piceatannol significantly inhibited VACV replication through both extracellular enveloped virus (EEV), and intracellular mature virus (IMV), with median effective concentrations (EC50) of 76.27 μM, and 63.93 μM, respectively. Further analysis revealed that piceatannol also reduced VACV entry and replication in HeLa cells. Molecular docking studies revealed a stable interaction between piceatannol and the palmitoylated F13 protein of VACV, with a calculated binding energy of−19.06 kcal/mol. This interaction suggests a mechanism by which piceatannol inhibits the generation of EEV. Additionally, piceatannol effectively limited the spread of VACV in cell cultures and exhibited significant virucidal effects on both the IMV and EEV forms. Collectively, our findings suggest that piceatannol holds promise as a therapeutic agent against orthopoxviruses infections by modulating key viral processes, warranting further exploration in clinical settings.